IMPLEMENTATION OF THE PROBLEM BASED LEARNING (PBL) MODEL TO IMPROVE STUDENT LEARNING OUTCOMES THE WRIGHTS BROTHERS MATERIAL IN CLASS X MIPA 2 SMA NEGERI 1 MOJOSARI - Sulastri Sulastri (Sean Institute, 2022)
The liveliness and creativity in thinking shown by class X MIPA 2 SMA Negeri 1 Mojosari in KKPI learning, especially the material of the wright brothers, is still low. Such as the low interest of students studying in groups, the implementation of learning in the field through group study is still rare, if any is implemented the results achieved are still low. In general, students tend to be passive, only receiving information conveyed by the teacher without being able to express opinions, ask questions, and answer questions. Therefore it is necessary to make improvements through a series of classroom action research activities with the aim of knowing the implementation or implementation of the problem based learning model , on the material material from the wright brothers in class X MIPA 2 SMA Negeri 1 Mojosari especially in the aspect of learning quality, student activity and student learning outcomes. The results of the study show that in the implementation or implementation of the problem based learning model on the material of the wright brothers class X MIPA 2 SMA Negeri 1 Mojosari can improve the quality of learning and student activity. This can be seen from the increase in the implementation score of lesson plans from 2.4 (adequate) in the first cycle to 3.45 (good) in the second cycle. In the aspect of student activity also increased from 77.78% (active) in the first cycle to 93.33% (very active) in the second cycle , and mastery learning outcomes increased from 69.44% in the first cycle to 88.89% in the second cycle.